Rural economic resilience: Empowering Pattiro Deceng MSMEs through strategic management, financial literacy, and digital adoption - Nur Rachma; Abdullah Abdullah; Arwita Irawati; Heeranah Heeranah (Community Empowerment, 2026)
Village economic empowerment is an important strategy in improving community welfare and strengthening local economic resilience through the optimization of regional potential. However, most MSME actors in rural areas still face various constraints, such as low managerial capacity, financial literacy, product innovation, and digital marketing utilization. This community service activity aims to strengthen the capacity of MSME actors in Pattiro Deceng Village, Maros Regency, through participatory training and assistance focusing on business management, simple financial management, product innovation, and the utilization of digital marketing. This program uses a participatory-educational approach through observation, interviews, workshops, direct assistance, and evaluation using a pre-test and post-test. The results of the activity showed a significant increase in the competence of participants after the program was implemented. Entrepreneurship understanding increased from 40% to 85%, while financial literacy and digital marketing capability also experienced a fairly significant increase. In addition, the number of MSMEs utilizing digital marketing platforms increased from 15% to 45% after the activity took place. These findings indicate that a participatory-based and hands-on practice empowerment approach is effective in improving MSME capacity, driving digital business transformation, and strengthening sustainable village economic development.